Student Morality Behavior: A Contribution of Social Godliness and Religiosity - Prasetiya, Benny; Agusti, Maulid; Halili, Heri Rifhan (Jurnal Pendidikan Agama Islam, 2021)
Society puts a great expectation on the importance of character education. Recently there is an imbalance between educational outcomes and other deviant behavior. This study was to explain the correlation of variables of the social godliness and religiosity in the family to the morality behavior of teenagers. The approach used was quantitative. The data were collected using a questionnaire. Test data analysis was carried out in the form of a pre-requisite analysis test (normality, linearity, and multicollinearity test) and hypothesis testing using linear regression analysis. The results showed that there was a positive influence on Social Godliness and Religiosity in the Family together on the moral behavior of teenage students. This was indicated by the F test result which obtained an F value of 13.544 with a significance of F 0.000 or F <0.05. The results of the multiple regression test showed that the coefficient of determination (r2) is 0.366. The coefficient of determination showed the large contribution of the two independent variables to the dependent variable. This contribution meant that social Godliness and religiosity in the family connect 36.6% of results of the Teenager Morality Behavior, while the remaining 63.4% was influenced by other variables which were not examined in this study.